TLC separation of methylated (-)-epigallocatechin-3-gallate - Ryszard Amarowicz; Anna Maryniak; Fereidoon Shahidi (Czech Journal of Food Sciences, 2005)
Methylated EGCG was separated from the crude extract using Sephadex LH-20 column chromatography with methanol as the mobile phase, and a semi-preparative HPLC method with water-dimethylformamide-methanol-acetic acid (157:40:2:1, v/v/v/v) as the mobile phase. The chemical structure of the separated catechin was confirmed by ESI-MS in the negative-ion mode. Three different mobile phases were used for silica gel and reversed phase TLC of EGCG and methylated EGCG. Rf values of both catechins were calculated and are reported. In the normal phase, the best condition of separation was with chloroform-methanol-water (65:35:10; v/v/v; lower phase) being used as the mobile phase. On octadodecylsilanised silica gel plates, the phase water-acetonitrile-methanol-acetic acid (79.5:18:2:0.5; v/v/v/v) offered the best separation of catechins.